Pengaruh Cita Rasa dan Promosi Melalui Media Sosial Terhadap Keputusan Pembelian Kopi - Suhailan Suhailan; Marlizar Marlizar; Ammar Fuad (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to examine the effect of taste and social media promotion on purchasing decisions among consumers of Matrana Coffee in Banda Aceh City. A quantitative approach was employed, with data collected through questionnaires and documentation. The sample consisted of 96 Matrana Coffee consumers, determined using the Purba formula and selected through probability sampling techniques. Data were analyzed using multiple linear regression analysis with t-test and F-test procedures. The findings reveal that taste has a positive and significant effect on purchasing decisions, as indicated by a t value of 2.533, which exceeds the t table value of 1.986. This finding suggests that product taste quality is able to shape positive consumer perceptions, thereby encouraging purchasing decisions. Social media promotion also shows a positive and significant effect on purchasing decisions, with a t value of 15.507 and a significance level of 0.000, indicating that the intensity of promotional activities through social media can increase consumer interest in the product. Simultaneously, taste and social media promotion significantly influence purchasing decisions, as evidenced by an F value of 165.918 and a significance level of 0.000 (<0.05). These results highlight important practical implications for coffee business owners in formulating marketing strategies that emphasize product quality and optimize the use of social media as a promotional tool to enhance consumers’ purchasing decisions.